A new raw material in the production of biodiesel: purple pinion seeds. - Fonseca, Aluísio Marques da; Carmo, Margareta do; Colares, Regilany Paulo; Valle, Camila Peixoto do; Oliveira, Sara Jane de; Alcócer, Juan Carlos Alvarado; Pinto, Olienaide Ribeiro de Oliveira; Santos, José Cleiton Sousa dos; Sousa, Emerson Yvay Almeida de; Silva, Francisco Felipe Maia da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Biodiesel is an alternative fuel that is produced through oil plants or animal fat. It is a renewable energy source, with biodegradable characteristics, to emit less pollutant than diesel. Thus, this work aims to show the production of biodiesel from the purple-pinion (Jatropha gossypiifolia L.) seeds. In addition to the synthesis, the physical-chemical characterization of both the raw material and the final product was carried out. The biodiesel synthetic route was performed by the basic catalytic transesterification reaction, using potassium hydroxide (KOH) in the presence of methanol (CH3OH) in the molar ratio of 1: 3 (oil: methanol). As a result, it was observed that the mass conversion of the biodiesel was 22.05 g. The physical-chemical analyzes carried out were acid index of 0.106 mgKOH / g, according to ANP technical resolution. The peroxide index of 1.03 meqO2 / kg, the kinematic viscosity of 20 ° C to 40 ° C, obtained was 6.455 mm2/s and 3.5343 mm2/s, the values are close to the ANP technique resolutions. Stability was 0.26 hours, and the biodiesel burning test was executed for approximately 3 hours. Therefore, there is a high viability of biodiesel production through the purple pinion seeds.